Hybrid core-shell nanoparticles: photoinduced electron-transfer for charge separation and solar cell application - Guchhait, Asim; Rath, Arup Kumar; Pal, Amlan J. (Chemistry of Materials, 2009)
We report growth and formation of hybrid core−shell nanoparticle systems, where photoinduced electron-transfer takes place from the II−VI semiconducting core to an organic shell. With the hybrid core−shell nanoparticles, we fabricate devices so that the photoinduced electron-transfer can finally yield photocurrent and result photovoltaic solar cells. Formation of an organic shell-layer on CdSe nanoparticles is supported by electronic absorption spectroscopy. Electron-transfer from the nanoparticle in the core to a number of organic molecules in the shell is established from quenching of photoluminescence intensity of CdSe nanoparticles as well as from a change in the lifetime of photoluminescence emission. Devices based on the hybrid core−shell nanoparticles in a suitable hole-transporting layer with two dissimilar metal electrodes show efficient photovoltaic performance. Here, following the electron-transfer, electrons flow through the organic molecules and holes, left in the nanoparticles, move through the hole-transporting polymer to the opposite electrodes to yield photovoltaic short-circuit current. The role of CdSe nanoparticles in light-harvesting and charge-generation has been substantiated by control experiments with ZnS nanoparticles in the core. In ZnS-based hybrid core−shell systems, photovoltaic performance is low since photoinduced electron-transfer does not occur from ZnS to the dye.